Peningkatan Kemampuan Gerak Dasar Melalui Permainan Tradisional Engklek, Lompat Tali Dan Gobak Sodor Untuk Anak Usia 5-6 Tahun Di Ra. Raudhatul Ummah Kota Bekasi - Usup Usup; Lilis Amperawati; Umi Harti; Umilia Umilia; Yunaini Yunaini; Durrotul Muniroh Ahdania (Jurnal Pendidikan Indonesia, 2022)
Education serves to improve the quality and quality of society so that they can live better. The educational process itself begins from the moment humans are born. The education provided must include all aspects of the development field such as cognitive, language, social, emotional, physical, motor and artistic so that children's abilities can develop optimally and thoroughly. Basic motion or fundamental motion is divided into three categories, namely locomotor, non-locomotor and manipulative motion. The basic movements that it develops occur in parallel with the growth of the body and the degree of maturity in children. Motion activity plays an important role for psychomotor development, cognitive abilities and affection abilities. In a play situation, children will show their talents, fantasies, and tendencies. When playing, children will internalize various emotional conditions that may arise such as a sense of pleasure, joy, tension, satisfaction, and perhaps a sense of disappointment. The game is a tool education because it gives a sense of satisfaction of joy and happiness